The power of social media in regional tourism development: a case study from Ōkunoshima Island in Hiroshima, Japan. Issue 18 (12th December 2018) - Usui, Rie; Wei, Xinyu; Funck, Carolin
Abstract : This research letter introduces a new insight into the power of social media in tourism development using a case study from Ōkunoshima Island in Hiroshima, Japan. The island has been experiencing an unprecedented tourism boom since 2014, when videos posted by social media led to an increase in international tourists in a formerly domestic destination. The results of our structured interviews suggest that tourists acquired information about the island through social media. This result implicated social media's power in developing tourism in peripheral regional areas, which are often left out from the international tourism circuit.